2021
DOI: 10.1101/2021.04.18.440341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in protein translation and carboxylic acid catabolic processes in diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) remains the leading cause of end stage kidney disease despite decades of study. Alterations in the glomerulus and kidney tubules both contribute to the pathogenesis of DKD although the majority of investigative efforts have focused on the glomerulus. We sought to examine the differential expression signature of human DKD in the glomerulus and proximal tubule and corroborate our findings in the db/db mouse model of diabetes. A transcriptogram network analysis of RNAseq data from la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(30 reference statements)
2
1
0
Order By: Relevance
“…The top-ranked enriched pathways for low eGFR are related to translation. Since low eGFR is an indicator of kidney disease, this is in line with studies reporting increased translational activity to several kidney diseases [30,31]. For diabetes and metabolic syndrome, which is a risk factor for diabetes, 16 out of the top 20 significantly enriched pathways were found for both outcomes.…”
Section: Gene Set Enrichment Analysissupporting
confidence: 82%
“…The top-ranked enriched pathways for low eGFR are related to translation. Since low eGFR is an indicator of kidney disease, this is in line with studies reporting increased translational activity to several kidney diseases [30,31]. For diabetes and metabolic syndrome, which is a risk factor for diabetes, 16 out of the top 20 significantly enriched pathways were found for both outcomes.…”
Section: Gene Set Enrichment Analysissupporting
confidence: 82%
“…The top-ranked enriched pathways for low eGFR are related to translation. Since low eGFR is an indicator of kidney disease, this is in line with studies reporting increased translational activity to several kidney diseases [17,18]. For diabetes and metabolic syndrome, which is a risk factor for diabetes, 16 out of the top 20 significantly enriched pathways were found for both outcomes.…”
Section: Gene Set Enrichment Analysissupporting
confidence: 82%
“…GO, and KEGG analyses were performed to reveal the role of candidate genes in the pathogenesis of AKI. GO analysis (Fig 4A ) revealed that candidate biomarker genes in biological processes were mainly enriched in the alpha-amino acid biosynthetic process [17][18][19] and the carboxylic acid biosynthetic process [20]; The molecular functions were mainly enriched in vitamin B and vitamin binding [21,22], amino acid binding [23,24] S-methyltransferase activity [25,26]; The cellular components were significantly enriched in brush border [27,28], apical plasma membrane [29,30], apical part of cell [31]. In addition, as shown in Fig 4B, KEGG analysis indicated that candidate genes were mainly enriched in Glycine, serine and threonine metabolism [32,33] Cysteine and methionine metabolism [34] and Biosynthesis of amino acids [35,36].…”
Section: Hub Gene Enrichment Analysismentioning
confidence: 99%